2008
DOI: 10.1111/j.1365-2036.2008.03650.x
|View full text |Cite
|
Sign up to set email alerts
|

Narrow band imaging with magnifying colonoscopy as diagnostic tool for predicting histology of early colorectal neoplasia

Abstract: SUMMARY BackgroundThe presence of abnormal microcapillaries detected by narrow band imaging (NBI) with magnifying colonoscopy has been reported to be a marker of colorectal neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(112 citation statements)
references
References 24 publications
1
111
0
Order By: Relevance
“…It has been reported that the capillary patterns observed by using NBI with magnifying endoscopy (NBI-ME) can help in assessing the degree of dysplasia in early colorectal neoplasia (Katagiri et al, 2008). Therefore, the present authors believe that NBI-ME provides a more accurate strategy than the conventional 'DISCARD' policy in which NBI is used without ME.…”
Section: 'Discard With Magnifying Endoscopy (Discard-me)' Policymentioning
confidence: 79%
See 1 more Smart Citation
“…It has been reported that the capillary patterns observed by using NBI with magnifying endoscopy (NBI-ME) can help in assessing the degree of dysplasia in early colorectal neoplasia (Katagiri et al, 2008). Therefore, the present authors believe that NBI-ME provides a more accurate strategy than the conventional 'DISCARD' policy in which NBI is used without ME.…”
Section: 'Discard With Magnifying Endoscopy (Discard-me)' Policymentioning
confidence: 79%
“…9), which has been reported to be useful for assessing the degree of dysplasia in early colorectal neoplasia (Katagiri et al, 2008). Lesions with invisible or faintly visible micro-capillary (MC) vessels are categorized as non-neoplastic (CP Type I), and lesions with clearly visible MC vessels are categorized as neoplastic.…”
Section: Diagnostic Criteria For the 'Discard-me' Policymentioning
confidence: 99%
“…The NICE classification with or without magnification is considered valid in the USA, Europe, and Japan for differentiating neoplastic and non-neoplastic polyps [33]. Regarding of IEE-ME techniques, there have been many studies on both NBI-ME and FICE-ME [12,13,17,23,[34][35][36]. These studies have reported accuracy of 93.…”
Section: Clinical Advantages Of Nbi and Ficementioning
confidence: 99%
“…Narrow-band imaging (NBI) of surface microvessels of colorectal lesions is useful for differentiating neoplasms from non-neoplasms and for predicting histopathological diagnosis (1)(2)(3)(4)(5)(6)(7)(8). We have reported that analysis of vascular patterns by magnifying NBI is useful for characterization of colorectal lesions (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%